Sticks or carrots? Comparing effectiveness of government shadow economy policies in Russia - Janis N. Kluge; Alexander Libman (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
Which incentives have the strongest impact on the size of the shadow economy? Is it about government's pressure against entrepreneurs operating in this sector, or is it about the benefits of legality? The goal of this paper is to explicitly contrast the role of sticks (court repressiveness) and carrots (financial aid to small and medium-sized firms) as factors determining the size of the shadow economy, using the case of the Russian taxi market. It uses a unique dataset of taxi licensing data from regional transport departments and indicators for taxi market demand to estimate the extent of informal business. When controlling for market demand, it finds a strong and robust positive effect of sanctions on the size of the official market, with higher repressiveness leading to a smaller shadow economy. In contrast, the effect of carrots was insignificant. The results suggest that the effectiveness of carrot policies is compromised when entrepreneurs operate informally to avoid dealing with corrupt bureaucrats and have low trust in the government.
urn:nbn:de:101:1-201703141334
Keywords: D73; D78; O17; 330; shadow economy; bureaucracy; corruption; development policy